PENGARUH PENDAPATAN BAGI HASIL MUDHARABAH, MUSYARAKAH DAN MURABAHAH TERHADAP BAGI HASIL TABUNGAN (STUDI PADA KSU BMT TAMAN SURGA JAKARTA) - Zaenudin Zaenudin (Faculty of Economic and Business, 2014)
This study aims to see whether the effect mudharabah and musyarakah income share, and also murabahah margin income at mudhabahah saving deposit product at BMT Taman Surga Jakarta. The method analysis that used in this study is linier regression, with each variabel tested both concurrently (simultaneously) or separately (partial). The result from this study is there is an positive and significat effect of mudharabah revenue sharing, musyarakah revenue sharing, and murabahah margin whether simultaneously and partial to mudharabah saving deposit share. BMT is expected to increase revenue for the results to further attract customers.DOI: 10.15408/etk.v13i1.1879